2020
DOI: 10.1002/mnfr.202000472
|View full text |Cite
|
Sign up to set email alerts
|

Sweetness Perception is not Involved in the Regulation of Blood Glucose after Oral Application of Sucrose and Glucose Solutions in Healthy Male Subjects

Abstract: Scope This study investigates the effect of the sweetness of a sucrose versus an isocaloric glucose solution in dietary concentrations on blood glucose regulation by adjusting the sweetness level using the sweet taste inhibitor lactisole. Methods and Results A total of 27 healthy males participated in this randomized, crossover study with four treatments: 10% glucose, 10% sucrose, 10% sucrose + 60 ppm lactisole, and 10% glucose + 60 ppm lactisole. Plasma glucose, insulin, glucagon‐like peptide 1, and glucagon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
1
Order By: Relevance
“…Carocho et al [ 38 ] reported that the caloric of 100 g glucose and sucrose led to different peaks in blood glucose concentration. Sucrose is a disaccharide, comprising one molecule of glucose and one molecule of fructose [ 39 ]. Therefore, sucrose is connected to the concentration of glucose in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Carocho et al [ 38 ] reported that the caloric of 100 g glucose and sucrose led to different peaks in blood glucose concentration. Sucrose is a disaccharide, comprising one molecule of glucose and one molecule of fructose [ 39 ]. Therefore, sucrose is connected to the concentration of glucose in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…There is also mixed evidence regarding the stimulation of cephalic phase responses by specific LES relative to caloric sweeteners (91)(92)(93) , though LES in general appear to have limited effects on post-prandial gut hormone or other physiological responses (94) . The post-ingestive responses to sugars reflect the nature of the carbohydrate, not the perceived sweetness (95) . Lastly, while it has been suggested that LES corrupt the natural relationship between sweetness and energy content, sweetness is poorly predictive of the energy content of human foods and diets, even when LES are excluded (96,97) .…”
Section: Low-energy Sweeteners V Sugarsmentioning
confidence: 99%
“…Lactisole ist eine Substanz, die an eine Untereinheit des Süßrezeptors bindet und so die Süßgeschmackswahrnehmung vermindert. Trotz unterschiedlicher Zuckerarten wiesen alle Test-Wissen lösungen mit und ohne lactisole den gleichen Energiegehalt auf [26].…”
Section: Süßrezeptor Und Kohlenhydratstoffwechselunclassified